Giant tortoises - Jaycox, Jaclyn, 1983- (2021)
"Giant tortoises can live for more than 100 years! These enormous creatures can also weigh a lot-more than 16 bicycles piled together. Find out all the facts about these peaceful island creatures"--
Includes bibliographical references and index.
Ages 6-8
Grades K-1
Keywords: Galapagos tortoise -- Juvenile literature; Aldabra tortoise -- Juvenile literature; Testudinidae -- Juvenile literature